1944
DOI: 10.1111/j.1365-2621.1944.tb16704.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Content of Tomatoes

Abstract: Since tomatoes are one of the commonly available sources of ascorbic acid, we thought that an investigation of some of the factors which affect the concentration of the vitamin i n this fruit would yield interesting results.It has been shown by numerous investigators that the ascorbic acid content of fruits and vegetables may vary under certain conditions. Among the factors reported by various investigators as being responsible for these fluctuations are the following : conditions of ripening by House, Nelson,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1947
1947
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…At low light intensities the increase of ascorbic acid content is linear to the increase of light intensity, and increased daylength has the same effect (Åberg 1946). No other Scandinavian or Finnish study was found on this subject, but in other countries it has been shown clearly that light increases the ascorbic acid content in apple (Johansson 1939, Kessler 1939, Murneek and Wittwer 1948, Murneek et al 1954), strawberry (Schuphan 1942, Hansen and Waldo 1944, Ezell et al 1947, Robinson 1949) and tomato (Kaski et al 1944, Brown 1955, Hamner et al 1945, McCollum 1946, Somers et al 1950, Murneek et al 1954). These studies showed that it is important that the apple, strawberry and tomato fruit itself is exposed to light, not only the plant leaves, and the amount of light close to the harvest period is especially important for high ascorbic acid content.…”
Section: Vitamin C / Ascorbic Acid In Plantsmentioning
confidence: 91%
“…At low light intensities the increase of ascorbic acid content is linear to the increase of light intensity, and increased daylength has the same effect (Åberg 1946). No other Scandinavian or Finnish study was found on this subject, but in other countries it has been shown clearly that light increases the ascorbic acid content in apple (Johansson 1939, Kessler 1939, Murneek and Wittwer 1948, Murneek et al 1954), strawberry (Schuphan 1942, Hansen and Waldo 1944, Ezell et al 1947, Robinson 1949) and tomato (Kaski et al 1944, Brown 1955, Hamner et al 1945, McCollum 1946, Somers et al 1950, Murneek et al 1954). These studies showed that it is important that the apple, strawberry and tomato fruit itself is exposed to light, not only the plant leaves, and the amount of light close to the harvest period is especially important for high ascorbic acid content.…”
Section: Vitamin C / Ascorbic Acid In Plantsmentioning
confidence: 91%
“…
Factors which affect the ascorbic acid content of fresh fruits may also account for the variations in ascorbic acid content of the canned and the frozen fruits. According to several investigators, Hamner, Bernstein, and Maynard (1945) ; Todhunter (1938) j Newman and Fellers (1940) ; Nagel and Harris (1943) ; Schroder, Satterfield, and IIolnies (1943) ;and Kaski, Webster, and Kirch (1944), these factors are variety, size, degree of ripening, duration and temperature of storage, light intensity, day length, temperature and fertilizer, picking, processing, extraction, freezing, and glass and tin containers.The comparative cost of serving frozen, fresh, and canned fruits as salads and desserts in a residence hall cafeteria was studied by Welch and Boney (1948). While fresh fruits in season were found to be lower in cost, canned fruits were higher than the frozen, with the exception of cherries and pineapple.
…”
mentioning
confidence: 99%
“…Factors which affect the ascorbic acid content of fresh fruits may also account for the variations in ascorbic acid content of the canned and the frozen fruits. According to several investigators, Hamner, Bernstein, and Maynard (1945) ; Todhunter (1938) j Newman and Fellers (1940) ; Nagel and Harris (1943) ; Schroder, Satterfield, and IIolnies (1943) ;and Kaski, Webster, and Kirch (1944), these factors are variety, size, degree of ripening, duration and temperature of storage, light intensity, day length, temperature and fertilizer, picking, processing, extraction, freezing, and glass and tin containers.…”
mentioning
confidence: 99%